Investigation of the structural, functional, and digestive properties of beta-casein from cow, goat, and donkey milk - Guiqin Liu; Ning Wang; Xue Chen; Yaqian Jin; Junnan Wan; Yanhao Zhao; Yiting Zhao; Cunfang Wang (Food Chemistry: X)
This study aimed to investigate the genotypes, structures, physicochemical properties, in vitro antioxidants, and digestive properties of isolated goat, donkey, and cow β-casein (β-CN). The β-CN genotypes of goats and donkeys are not cow type A1 β-CN, avoiding the unfavorable effects on intestinal digestion of BCM-7, a peptide fragment produced by the digestion of cow type A1 β-CN from bovine milk. Goat and donkey β-CN exhibited a smaller particle size, a more stable solution system, a looser secondary structure, and better solubility than cow β-CN. The microstructural findings from simulations of in vitro digestion in infants revealed that goat β-CN exhibited superior digestibility, characterized by reduced flocculation and a more loosely organized protein structure during the gastric digestion phase. Furthermore, the degree of hydrolysis indicated that both goat and donkey β-CN were significantly more readily digested compared to cow β-CN. Moreover, donkey β-CN gastrointestinal digests possessed significant anti-free radical activity.